UJI BEBERAPA KONSENTRASI Beauveria bassiana Vuillemin LOKAL DALAM MENGENDALIKAN HAMA KEPIK HIJAU (Nezara viridula L.) (Hemiptera: Pentatomidae) PADA TANAMAN KEDELAI (Glycine max L.) - David Afrinda; Desita Salbiah; J. Hennie Laoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Nezara viridula is a pest that can reduce soybean production both in quality and quantity. Currently efforts in controlling N. viridula still use synthetic chemical insecticides that can have negative impacts. One solution to reduce reliance on synthetic chemical insecticide is the use of entomopathogenic fungi Beauveria bassiana. The purpose of this study was to test the ability of several concentrations of entomopathogenic fungi Beauveria bassiana Vuillemin Riau local green ladybugs for pest control N. viridula on soybean plants. Research prepared using completely randomized design (CRD) with 6 treatments and 4 replications. The treatment used is some concentration of B. bassiana consists of 6 treatments are: 0 g/ l of water, the concentration of B. bassiana 70 g / l of aquades, the concentration of B. bassiana 75 g / l of aquades, the concentration of B. bassiana 80 g / l of aquades , the concentration of B. bassiana 85 g / l of aquades, the concentration of B. bassiana 90 g / l of aquades. The results showed concentrations of B. bassiana 90 g / l of aquades is more effective in controlling N. viridula, but to fulfill the concept of integrated pest control concentration of 80 g / l of aquades (17.42 x 107 kon / ml) are considered better because it can lead to early N. viridula death for 64.25 hours, lethal time 50 (LT50) for 135.75 hours, and caused total mortality 85% for 9 days (209 hours). Keyword: Beauveria bassiana , Nezara viridula, Soy bean, biological control